Genetic behavior of rice (Oryza sativa) genotypes under normal and infested weed conditions - M S, Abd EL-Aty; M A, El Hity; Abo-Youssef, M I; Abo Omar, M A; Kamara, M M (The Indian Journal of Agricultural Sciences, 2020)
A field study was conducted at Sakha Agricultural Research Station, Kafr El-Sheikh, Egypt during 2016-17 summer, to estimate general (GCA) and specific (SCA) combining ability effects as well as identify type of gene action controlling the inheritance of the studied traits under normal and infested weed conditions. Seven a diverse rice (Oryza sativa L.) parent’s were crossed using half diallel cross method without reciprocals to produce 21 F1 crosses during 2016 season. The seven parents and their 21 F1 crosses were evaluated under normal and infested weed conditions using a randomized complete block design (RCBD) with three replications during 2017. Highly significant differences were observed among genotypes, parents and crosses for all the studied traits. Moreover, general combining ability (GCA) and specific combining ability (SCA) mean squares were highly significant for all the studied traits under both conditions. The best general combiner for earliness and short stature was Sakha 103 variety. The highest desirable SCA effects were obtained by the crosses; Egyptian Yasmin × Dullar, Sakha 104 × Egyptian Yasmin, Egyptian Yasmin × Rikuto Norin 22 and Giza 177 × Rikuto Norin 22 for flag leaf area, No. of panicles/plant and grain yield/plant. These crosses could be utilized in rice breeding program for improving grain yield trait under normal and infested weed conditions.